Adjuvant treatment and outcome of stage III melanoma patients: results of a multicenter real-world German Dermatologic Cooperative Oncology Group (DeCOG) study - Lodde, Georg Christian; Hassel, Jessica C.; Wulfken, Lena Margarethe; Meier, Friedegund; Mohr, Peter; Kähler, Katharina C.; Hauschild, Axel; Schilling, Bastian; Loquai, Carmen; Berking, Carola; Hüning, Svea; Eckardt, Julia; et al. (European journal of cancer, 2023)
Purpose - Clinical trials demonstrated significantly improved recurrence-free survival (RFS) of melanoma patients receiving adjuvant treatment. As data from controlled trials are based on selected populations, we investigated adjuvantly treated stage III melanoma patients under real-world conditions. - Patients and methods - In a prior multicenter cohort study, stage III-IV melanoma patients were analysed for their choice of adjuvant therapy. In this follow-up study, we examined RFS, overall and melanoma-specific survival (MSS) and response to the subsequent treatment of 589 stage III patients (232 BRAF-mutated) receiving adjuvant PD-1 inhibitors (PD1; n = 479) or targeted therapy (TT; n = 110). - Results - The median follow-up of the total cohort was 25.7 months. The main reason for premature discontinuation of adjuvant therapy was disease progression in PD1- (28.8%, n = 138/479) and adverse events in TT-treated patients (28.2%, n = 31/110). Among BRAF-mutated patients, RFS at 24 months was 49% (95% CI 40.6-59.0%) for PD1- and 67% (95% CI 58-77%) for TT-treated patients. The risk of recurrence was higher for BRAF-mutated PD1 than TT (hazard ratio 1.99; 95% CI 1.34-2.96; hazard ratio adjusted for age, sex and tumour stage, 2.21; 95% CI 1.48-3.30). Twenty-four months MSS was 87% (95% CI 81.0-94.1) for PD1 and 92% (95% CI 86.6-97.0) for TT. Response to subsequent systemic treatment for unresectable disease was 22% for all PD1- and 16% for TT-treated patients. - Conclusions - PD1-treated patients had more and earlier recurrences than TT patients. In BRAF-mutated patients, adjuvant TT might prevent early recurrences more effectively than PD1 treatment. Management of recurrence despite adjuvant treatment is challenging, with low response to current therapeutic options.
Gesehen am 20.11.2023